Strategi Promosi Pustakawan di Perpustakaan Balai Bahasa Padang - Rahmi, Lailatul; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2012)
The purpose of this study was (1) to describe the promotion strategies undertaken by the Library Hall of Languages ​​Padang. (2) describing the obstacles encountered in the promotion of Library Hall of Languages ​​Padang. (3) describe problem solving in the face of obstacles promotional Language Institute Library Padang. Data through observation and interviews with librarians Library Language Institute Padang. Data collection was done descriptively. The findings of the study: first, pomosi strategies that exist in Padang Language Center Library include: establish communication with pemustaka, build cooperation with third parties, Constructing promotion programs, and work plan. Second, the constraints faced by the Library Hall of Languages ​​Padang in library promotion are: (1) human resources, (2) limited funds, (3) facility. Third, efforts Library Hall Padang to overcome language barriers are: (1) human resources, (2) limited funds, (3) facility. Keywords: promotion strategies; library promotions